Penerapan Metode Vak Pada Game Edukasi Mengenal Huruf Hijaiyah Dengan Algoritma Fisher Yates Berbasis Android - Asep Arwan; Yuliano Reismanda (Jurnal SIGMA, 2022)
Religious knowledge, especially hijaiyah for children, is very important as a rovision for the basis of their lives in facing life in the future. One of the benefits of the game is that it can be a medium of learning for children. In order for educational games to be more interesting when played, the authors apply one of the methods of developing the Multimedia Development Live Cycle (MDLC) which includes the concept, design, material collecting, assembly, testing and distribution stages. From the test results using black box, the system in the application works as expected. In this research, a problem is formulated on how to implement the Fisher Yates algorithm. The results of the questionnaire from 10 respondents stated that 92% agreed with the problems that had been described. As a solution to this problem, it is proposed to design an educational game "Knowing Hijaiyah Letters" to help foster children's interest in learning to recognize Hijaiyah letters with fun learning media. The use of multimedia-based educational programs that combine digital sound. In this study, the development of interactive learning media using the Visual Auditory Kinesthetic (VAK) learning approach was carried out. With this approach children can learn with the senses of sight, hearing, and movement. Keywords: Learning Media, Educational Games, Hijaiyah Letters, 2D Games